Partial Hydatidiform Mole with Subclinical Hyperthyroidism - A Case Report - R. Fuad Mustaqim; Aditiyono Aditiyono; Gatot N.A. Winarno; Dalri Muhammad Suhartomo (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Partial hydatidiform mole is a rare gestational trophoblastic disease marked by triploid karyotype, fetal abnormalities, and growth disorders, sometimes accompanied by subclinical hyperthyroidism. Diagnosis relies on β-hCG testing, ultrasound, and immunohistochemistry. Management, especially regarding chemotherapy, remains debated due to fertility concerns. This case report presents a rare instance of partial hydatidiform mole with subclinical hyperthyroidism, emphasizing key diagnostic and therapeutic considerations. A case report 22-year-old primigravida at 16 weeks presented with abortion imminens, placentomegaly, anemia, and massive bleeding. Evaluation confirmed a partial mole with subclinical hyperthyroidism. She was stabilized for hemorrhagic shock and IUFD, then underwent molar evacuation and caesarean hysterectomy. Although chemotherapy was initially planned, β-hCG levels normalized within 4 months without it, and follow-up showed no malignant transformation or recurrence. Low-risk partial hydatidiform mole can regress without chemotherapy, but comorbidities like subclinical hyperthyroidism require attention. At least 6 months of β-hCG monitoring is essential to confirm resolution and detect complications. Keyword: Chemotherapy, Hyperthyroid Subclinical, Partial Hydatidiform Mole.